Generation of induced pluripotent stem cell line ICGi018-A from peripheral blood mononuclear cells of a patient with Huntington's disease - A.A. Malakhova; E.V. Grigor'eva; T.B. Malankhanova; S.V. Pavlova; K.R. Valetdinova; N.Yu. Abramycheva; A.S. Vetchinova; S.N. Illarioshkin; S.M. Zakian (Stem Cell Research, 2020)
Huntington's disease (HD) is an autosomal dominant neurodegenerative disease caused by CAG repeat expansion in the HTT gene. HD patient-specific induced pluripotent stem cells (iPSCs) represent an excellent model for the disease study. We generated iPSC line from blood mononuclear cells of HD patient with 38 CAG repeats in the HTT exon 1 using integration free episomal plasmids expressing Yamanaka factors. The iPSC line retained the disease causing mutation and expressed pluripotency markers. It also displayed a normal karyotype and the ability to differentiate into derivatives of three germ layers.